Consumption of sugar-sweetened beverages and T2D diabetes in the Eastern Caribbean - Carol R Oladele; Neha Khandpur; Deron Galusha; Saria Hassan; Uriyoán Colón-Ramos; Mary Miller; Oswald P Adams; Rohan G Maharaj; Cruz M Nazario; Maxine Nunez; Rafael Pérez-Escamilla; Trevor Hassell; et al. (Cambridge University Press, 2023)
Abstract Objective: Sugar-sweetened beverages (SSB) are implicated in the increasing risk of diabetes in the Caribbean. Few studies have examined associations between SSB consumption and diabetes in the Caribbean. Design: SSB was measured as teaspoon/d using questions from the National Cancer Institute Dietary Screener Questionnaire about intake of soda, juice and coffee/tea during the past month. Diabetes was measured using self-report, HbA1C and use of medication. Logistic regression was used to examine associations. Setting: Baseline data from the Eastern Caribbean Health Outcomes Research Network Cohort Study (ECS), collected in Barbados, Puerto Rico, Trinidad and Tobago and US Virgin Islands, were used for analysis. Participants: Participants (n 1701) enrolled in the ECS. Results: Thirty-six percentage of participants were unaware of their diabetes, 33% aware and 31% normoglycaemic. Total mean intake of added sugar from SSB was higher among persons 40-49 (9·4 tsp/d), men (9·2 tsp/d) and persons with low education (7·0 tsp/d). Participants who were unaware (7·4 tsp/d) or did not have diabetes (7·6 tsp/d) had higher mean SSB intake compared to those with known diabetes (5·6 tsp/d). In multivariate analysis, total added sugar from beverages was not significantly associated with diabetes status. Results by beverage type showed consumption of added sugar from soda was associated with greater odds of known (OR = 1·37, 95 % CI (1·03, 1·82)) and unknown diabetes (OR = 1·54, 95 % CI (1·12, 2·13)). Conclusions: Findings indicate the need for continued implementation and evaluation of policies and interventions to reduce SSB consumption in the Caribbean.